TINJAUAN YURIDIS SENGKETA WARISAN DALAM PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN WARGA NEGARA ASING - Airin Titus; Selamat Lumban Gaol (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Mixed marriages between Indonesian citizens (WNI) and foreign citizens (WNA) are a growing phenomenon in line with the development of globalization and mobility between countries. This condition not only creates social dynamics but also presents various legal issues, particularly in the field of inheritance. This study aims to analyze the inheritance law regulations in mixed marriages and examine the legal issues that arise in inheritance disputes involving Indonesian citizens and foreign nationals. The research method used is normative juridical research with a statutory and conceptual approach. Legal materials were obtained through literature studies covering relevant laws and regulations, doctrines, and court decisions, then analyzed qualitatively. The results of the study indicate that the inheritance law system in Indonesia is pluralistic, consisting of Islamic inheritance law, customary inheritance law, and Western civil inheritance law, the application of which depends on the religion, citizenship status, and legal system applicable to the parties. In the context of mixed marriages, inheritance disputes often arise due to differences in citizenship, religious differences, the citizenship status of children, and restrictions on land ownership rights by foreign nationals based on the Basic Agrarian Law. Furthermore, the lack of specific regulations regarding inheritance in mixed marriages creates legal uncertainty and the potential for cross-border legal conflicts. Therefore, a more comprehensive legal regulation regarding inheritance in mixed marriages is needed to provide legal certainty and protection for all parties, particularly for children born of mixed marriages.